Factors Affecting Contraceptive Use Among The Women Of Reproductive Age In Samarahan District, Sarawak, Malaysia - Dianna, Anak Jawa; Md Mizanur, Rahman (Malaysian Journal of Public Health Medicine, 2015)
The Contraceptive Prevalence Rate (CPR) is an important indicator in achieving the Millennium Development Goal (MDG) by 2015. Despite all the efforts to improve the CPR in Malaysia after 1994, it has levelled off at the range of 52% since then. Considering this view, the present study was to determine prevalence of contraceptive use and also to determine the factors affecting it. This cross sectional study involving a total of 462 married women of reproductive aged 18 to 49 years. Data were collected by face to face interview using a semi-structured questionnaire. All completed questionnaires were validated manually and data analysis carried out by computer using IBM SPSS version 19.0 software. The prevalence of contraceptive use was found to be 43%. The most commonly used contraceptive method was oral contraceptive pills (55%) followed by injectable contraceptives (23%), and female sterilization (11%). Binary logistic regression analysis revealed that women aged less than 25 years (OR=6.0, 95% CI: 1.94, 18.49), husband-wife discussion about family planning issues (OR=4.3, 95% CI: 2.23, 8.18) and last child aged one year (OR=2.2, 95% CI: 0.98, 4.69) were potential factors for contraceptive use (p<0.05). The study emphasizes the importance of husband-wife communication, shared responsibility and promotes their active involvement in family planning programmes to ensure a long-term permanent effect on contraceptive use.